Deepening democracy for sustainable development: An assessment of the presidential system of government in Nigeria (West African Journal on Sustainable Development, 2024)
Nigeria is yet to utilize its intrinsic potentials for effective transformation of the economy, leading to endless conversations on the possible causation of the absence of tangible development in various aspects of the economy. Nevertheless, there were suggestions that the operationalization of the presidential system of democratic administration impedes sustainable development in Nigeria because of its resultant high cost on governance implications. Recent debates on the appropriate democratic system of administration that the country should adopt have focused more on whether Nigeria should continue with the presidential system or revert to the previous parliamentary type adopted at the wake of independence for sustainable development. In essence, much literature on government and development has not paid adequate attention to the impact of the presidential system on sustainable development in Nigeria. Thus, the inability of the system to transform the economy and activate the necessary economic and political indicators required for sustainable development led to gaps in the socio-economic and political development in Nigeria. Essentially, this study attempts to examine the presidential system in relation to its impact on capital expenditures. Consequently, secondary sources of data collection were used to explore information from government, democracy, and sustainable development literature, journals, textbooks, official documents, news articles, and internet sources. Key informant interviews were conducted with key democratic institutions and individuals, and the gathered data was qualitatively analyzed using the content analysis method. The study shows a significant level of influence of the above identified issues on sustainable development in Nigeria. The paper, concludes that the presidential system of democratic administration in Nigeria is fraught with an overbloated structure that exerts a burden of high cost of governance implications on the economy. However, the reduction in size and structure of the presidential system reduces recurrent expenditure, and funds are saved through increased funding for capital projects. Thus, issues impeding sustainable development are being addressed.
Keywords: Presidential System; Democracy; Sustainable Development; Parliamentary system; Government